Does Luxury Brand Perception Matter In Purchase Intention? A Comparison Between A Japanese Brand And A German Brand - Sari, Diana; Kusuma, Brata (ASEAN Marketing Journal, 2021)
The research regarding luxury products in developed economies can be found in many literatures, nevertheless similar research in developing economies are still limited. Since this topic is still underexplored, particularly in developing economies, the purpose of this study is to investigate Indonesian consumers’ perception of two different luxury brands that comes from different countries, namely BMW (Germany) and Lexus (Japan). Data was collected from diverse Indonesian BMW and Lexus owners. The consumers’ general brand perception and perceived values of luxury car are examined in this study. Data analysis used structural equation modeling (SEM). Results indicated that Indonesian consumers considered Japanese luxury car’s (Lexus) conspicuous value higher than German luxury car (BMW). Nevertheless, BMW was considered to have higher value in all of the rest of the aspects studied such as quality value, social value, and hedonic value. Even though so, the result of the study finds that Lexus owners have a higher purchase intention than BMW owners. The research concludes that luxury brand perception is highly affecting consumers’ purchase intention in this luxury automotive industry.